Infection hospitalization increases risk of dementia in the elderly - Tate, Judith A; Snitz, Beth E; Alvarez, Karina A; Nahin, Richard L; Weissfeld, Lisa A; Lopez, Oscar; Angus, Derek C; Shah, Faraaz; Ives, Diane G; Fitzpatrick, Annette L; Williamson, Jeffrey D; Arnold, Alice M; et al. (Critical care medicine, 2014)
Severe infections, often requiring ICU admission, have been associated with persistent cognitive dysfunction. Less severe infections are more common and whether they are associated with an increased risk of dementia is unclear. We determined the association of pneumonia hospitalization with risk of dementia in well-functioning older adults. Secondary analysis of a randomized multicenter trial to determine the effect of Gingko biloba on incident dementia. Five academic medical centers in the United States. Healthy community volunteers (n = 3,069) with a median follow-up of 6.1 years. None. We identified pneumonia hospitalizations using International Classification of Diseases, 9th Edition-Coding Manual codes and validated them in a subset. Less than 3% of pneumonia cases necessitated ICU admission, mechanical ventilation, or vasopressor support. Dementia was adjudicated based on neuropsychological evaluation, neurological examination, and MRI. Two hundred twenty-one participants (7.2%) incurred at least one hospitalization with pneumonia (mean time to pneumonia = 3.5 yr). Of these, dementia was developed in 38 (17%) after pneumonia, with half of these cases occurring 2 years after the pneumonia hospitalization. Hospitalization with pneumonia was associated with increased risk of time to dementia diagnosis (unadjusted hazard ratio = 2.3; CI, 1.6-3.2; p < 0.0001). The association remained significant when adjusted for age, sex, race, study site, education, and baseline mini-mental status examination (hazard ratio = 1.9; CI, 1.4-2.8; p < 0.0001). Results were unchanged when additionally adjusted for smoking, hypertension, diabetes, heart disease, and preinfection functional status. Results were similar using propensity analysis where participants with pneumonia were matched to those without pneumonia based on age, probability of developing pneumonia, and similar trajectories of cognitive and physical function prior to pneumonia (adjusted prevalence rates, 91.7 vs 65 cases per 1,000 person-years; adjusted prevalence rate ratio = 1.6; CI, 1.06-2.7; p = 0.03). Sensitivity analyses showed that the higher risk also occurred among those hospitalized with other infections. Hospitalization with pneumonia is associated with increased risk of dementia.